1991
DOI: 10.1021/jo00011a034
|View full text |Cite
|
Sign up to set email alerts
|

Deprotection of carboxylic esters of .beta.-lactam homologs. Cleavage of p-methoxybenzyl, diphenylmethyl, and tert-butyl esters effected by a phenolic matrix

Abstract: p-Methoxybenzyl, diphenylmethyl, and tert-butyl esters were deprotected by gentle heating in phenol. This method of ester cleavage played an important role in p-ladam synthesis. The mechanism of the reaction is believed to involve a proton relay through a hydrogen-bonded phenolic matrix.(7) A precedent exista in the case of the hydrolysis of N-(benzyloxycarbonyl)-L-proline benzhydryl ester by TFA and phenol. However, a relatively large amount of TFA (1 mL) and phenol (0.2 g) were used to cleave 0.41 g (1 mmol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…The use of an electron-rich aromatic system as an additive to minimize the formation of side products is common when near stoichiometric amounts of TFA are utilized, with anisole being typically employed for this purpose. 70 Substoichiometric amounts of TFA have also proven to be effective when phenol was used as the solvent at elevated temperatures (45 °C). 71 The nucleophilic additives and/or solvents are presumed to function as cation scavengers, reacting with the 4-methoxybenzyl cation generated in the transformation which protects the substrate from side reactions.…”
Section: Deprotection Of Pmb Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of an electron-rich aromatic system as an additive to minimize the formation of side products is common when near stoichiometric amounts of TFA are utilized, with anisole being typically employed for this purpose. 70 Substoichiometric amounts of TFA have also proven to be effective when phenol was used as the solvent at elevated temperatures (45 °C). 71 The nucleophilic additives and/or solvents are presumed to function as cation scavengers, reacting with the 4-methoxybenzyl cation generated in the transformation which protects the substrate from side reactions.…”
Section: Deprotection Of Pmb Estersmentioning
confidence: 99%
“…4 Subsequent investigations on β-lactam antibiotics demonstrated that in some cases, PMB esters could be cleaved by heating the substrate to 60 °C in neat phenol without the addition of a stronger acid. 70 This method was particularly useful for the deprotection of acid-sensitive substrates, such as β-lactam 72 (Scheme 19). The deprotection of PMB ester 72 failed with many other methods (anisole/TFA, neat formic acid, or anisole/AlCl 3 ) due to the sensitivity of the β-lactam ring.…”
Section: Deprotection Of Pmb Estersmentioning
confidence: 99%
“…However, synthesis of GPRA from p -methoxybenzyl-7phenylacetylamino-3-propenyl-3-cephem-4carboxylate (GPRE) is also an important step in the industrial process. To remove the p -methoxybenzyl group of GPRE, the method currently used involves environmental toxicants such as trifl uoroacetic acid and phenol, which have signifi cant disposal costs (Torii et al 1991). A low temperature, below 5 ° C, is needed to avoid producing trans -GPRA which is much less valuable than cis -GPRA because ciscefprozil is much more effective than trans -cefprozil.…”
Section: Introductionmentioning
confidence: 99%
“…Because it was already reported that although the ∆ 3 isomer can readily equilibrate under basic conditions with the ∆ 2 isomers, the free acids can also equilibrate at a relatively lower rate, 5(a) and a shortened reaction time was tried compared with that of the literature. 8 Interestingly, neither the ∆ 3 →∆ 2 isomerization nor the Michael adduct was not detected in the crude reaction mixture prior to purification. Thus, protocol was developed for purification of final product.…”
mentioning
confidence: 99%
“…Initially, the final protected intermediate was deprotected for 1 hour in neat TFA to remove both t-butyl and p-methoxybenzyl (PMB) protecting groups. 8 The TFA was removed imme- diately by azotroping with toluene. The product was purified either by silica gel chromatography using a gradient of methanol in methylene chloride or by HPLC using a gradient of acetonitrile and water.…”
mentioning
confidence: 99%